Odpowiedź :
2x+1 - pierwsza liczba
2x+3 - druga liczba
(2x+3)²-(2x+1)²=4x²+12x+9 -(4x²+4x+1)=4x²+12x+9-4x²-4x-1=8x=8
(2x+1+2x+3)*2=8x+8
Pozdro)))
2x+3 - druga liczba
(2x+3)²-(2x+1)²=4x²+12x+9 -(4x²+4x+1)=4x²+12x+9-4x²-4x-1=8x=8
(2x+1+2x+3)*2=8x+8
Pozdro)))
bo 2 razy n to jest parzysta, czyli 2n - 1 i 2n+1 to l. nieparz.
(2n-1)² - (2n+1)² = 4n² - 4n + 1 - 4n² - 4n - 1 = -8n
2n-1+2n+1 = 4n
2 x 4n = 8n
8n ≠ -8n
(2n-1)² - (2n+1)² = 4n² - 4n + 1 - 4n² - 4n - 1 = -8n
2n-1+2n+1 = 4n
2 x 4n = 8n
8n ≠ -8n